Histopathological changes in rat model with oral candidiasis - Mustafa Al-Ahmad, Basma Ezzat (2019)
Clinical studies indicating differences in host susceptibility to Candida biofilm-associated infections, For example, denture stomatitis, a device-associated infection in which the clinical biofilm may be both mucosal and device associated this is common in immunocompetent patients . Studies suggest that the biofilm lifestyle protects fungi from host recognition. Studies suggest that the biofilm lifestyle protects fungi from host recognition. A prominent feature of biofilm infections is infiltration of adjacent tissues by neutrophils. Neutrophils swarm into the biofilm mass in mucosal surface biofilms formed by Candida albicans ,however, their activation state within biofilms is unknown From a histopathological and diagnostic point of view, most of the lesions described in animal models have faithfully reproduced human candidal lesions .